Data Ownership: Who Owns 'My Data'? (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2012)
The amount of data in our world today is substantially mammoth. Many of the personal and non-personal aspects of our day to day activities are aggregated and stored as data by both businesses and governments. The increasing data captured through multimedia, social media, and the Internet of Things is a phenomenon that needs to be properly examined. In this article, we explore this topic, and analyse the term data ownership. We aim to raise awareness and trigger debate for policy makers around data ownership and the need to improve existing data protection and privacy laws and legislation at both national and international levels.